2020
DOI: 10.1111/jace.17149
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature phase and microstructure evolution of polymer‐derived SiZrCN and SiZrBCN ceramic nanocomposites

Abstract: Ultra-high temperature ceramics (UHTCs) are proposed to be the most promising material candidates for structural and thermal protection components in the aerospace field, due to their extremely high melting points, high hardness and strength, good thermal and chemical attack resistance. 1-4 When considering engineering manufacturing and application in very harsh environment, silica formers (silicon-containing materials such as SiC, Si 3 N 4 , SiBCN, MoSi 2 , TaSi 2 etc) are generally introduced into UHTCs to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 53 publications
(168 reference statements)
4
35
1
Order By: Relevance
“…25,55 The phase composition of SiCN, SiZrCN and SiZrBCNbased sintering aids in the densified monolithic ZrB 2 samples seems to be slightly different than that found in the neat materials as exposed to similar thermal treatment condition, as reported recently. 25 Thus, SiCN, SiZrCN, and SiZrBCN exposed to 1700℃ in N 2 atmosphere were shown to consist of mainly β-SiC/C as for SiCN and of ZrC(N), β-SiC, β-Si 3 N 4 as for SiZrCN and SiZrBCN. 25 Additionally, a turbostratic graphite-like BCN phase was unambiguously found in SiZrBCN, 25 similar to the finding made in the present work in ZrB 2 /SiZrCN and ZrB 2 /SiZrBCN.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations
“…25,55 The phase composition of SiCN, SiZrCN and SiZrBCNbased sintering aids in the densified monolithic ZrB 2 samples seems to be slightly different than that found in the neat materials as exposed to similar thermal treatment condition, as reported recently. 25 Thus, SiCN, SiZrCN, and SiZrBCN exposed to 1700℃ in N 2 atmosphere were shown to consist of mainly β-SiC/C as for SiCN and of ZrC(N), β-SiC, β-Si 3 N 4 as for SiZrCN and SiZrBCN. 25 Additionally, a turbostratic graphite-like BCN phase was unambiguously found in SiZrBCN, 25 similar to the finding made in the present work in ZrB 2 /SiZrCN and ZrB 2 /SiZrBCN.…”
Section: Methodsmentioning
confidence: 54%
“…No references were found on modeling for CMCs, though experimental studies o ing process have been reported. Studies o derived SiC ceramic 25 and SiC/SiC c shown that porosity decreases and mecha prove with the increasing number of PIP show that increasing pyrolysis temperatu tration of SiC fillers in polycarbosilane improved mechanical properties in two-d SiC (C/SiC) composites fabricated using Starting with pyrolysis of a "cured prepreg-based composite, each processin process involves infiltration of a precera porous ceramic preform followed by a py which the polymer is converted into ceram cess modeling is focused on these two ste Modeling of infiltration of liquids in well-studied subject, especially in the where it is used to model seepage of wa soils and rocks. 29,30 The physics of resin under pressure is similar to the seepage pr lar approaches have been used also to mod into a mold containing fiber mats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31,32] For instance, Zr doping to SiCN lead to the precipitation of t-ZrO 2 phases, which reinforces the nanocomposites and hence enhances thermal stability towards crystallization, oxidation and corrosion even at temperatures above 1300 o C. [27,28,33] B-doping into SiCN ceramic resulted in the high temperature stability towards crystallization up to temperature as high as 2200 o C. [14,34] Further, incorporation of B into SiZrCN ceramics diminishes the crystallization of ZrC x N y and suppress the reaction of SiN x with C, resulting in an improved thermal stability of SiZrBCN as compared to SiZrCN ceramics. [35] Hf-doping to the SiCN matrix improved the thermal stability as well as oxidation and corrosion resistance. [5,13,36] A new class of SiC/Hf y Ta 1−y C x N 1−x /C nanocomposite with improved oxidation resistance was synthesized at 1900 o C, and the composition as well as thickness of the HfC x N 1−x and TaC x N 1−x core shell structures can be tuned with varying the Hf:Ta atomic ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting polymer-derived ceramics (PDCs) are monophasic or undergo phaseseparation leading to PDC-nanocomposites, depending on the composition and processing of the precursor. 1 Numerous PDCs have been investigated in the past years and were shown to exhibit good creep and oxidation resistance, 2 exceptional temperature stability, 3,4 or interesting functional properties such as high piezoresistivity, 5 biocompatibility, 6 or sensing capabilities, 7 offering promising aspects for future research and applications. One of the most compelling attributes of polymer precursors is that they can be chemically and structurally modified with, for instance, metal complexes or functional groups; accordingly, allowing to tailor the properties of the resulting ceramics to the needs of their respective application.…”
Section: Introductionmentioning
confidence: 99%